A metagenomic analysis displays the diverse microbial community of a vermicomposting system in Uganda. Issue 1 (1st January 2016) - Blomström, Anne-Lie; Lalander, Cecilia; Komakech, Allan John; Vinnerås, Björn; Boqvist, Sofia
Abstract : Background: Vermicomposting is a mesophilic process using earthworms to efficiently and at low cost process large volumes of organic waste. It has been suggested to not only increase soil fertility but also increase biomass of beneficial bacteria while reducing harmful bacteria. The aim of this study was to set up a strategy to investigate and characterise the viral as well as the bacterial composition of a vermicomposting system. Material and methods: The vermicomposting unit used in this study was placed at the Makerere University Agricultural Research Institute Kabanyolo on the outskirts of Kampala, Uganda, and was fed with 80% cattle manure and 20% food waste. On Day 172, the compost was terminated and compost samples were collected from three layers of the unit: the top, the middle and the bottom layer. A metagenomic approach was then applied to characterise the viral and bacterial composition of the vermicomposting system. Results and discussion: A high abundance and diversity of bacteria were identified. Proteobacteria was the largest phyla in the compost (mainly Alpha-, Gamma- and Betaproteobacteria), constituting almost 65% of the bacterial reads in the data sets. DNA samples from several possible pathogenic bacteria, such as Salmonella spp., Escherichia coli, Enterobacter spp., Enterococcus spp. and Clostridium spp, were detected in the vermicompost, suggesting that there might still be harmful bacteria in the vermicast. Phages constituted the main viral group; apart from phages, mainly insect viruses were identified. The only animal or human virus identified was kobuvirus. In summary, metagenomic analysis was shown to be an efficient technology to characterise the microbial composition of vermicast. The data from this study contribute to a better understanding of the microbes present in this kind of composting system and can help determine measures necessary for safe manure handling.